2022
DOI: 10.1007/s10528-022-10206-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Hub Genes and the Signaling Pathways in Human iPSC-Cardiomyocytes Infected by SARS-CoV-2

Abstract: Severe Acute Respiratory Syndrome Coronavirus Type 2 (SARS-CoV-2) is an enveloped single-stranded RNA virus that can lead to respiratory symptoms and damage many organs such as heart, kidney, intestine, brain and liver. It has not been clearly documented whether myocardial injury is caused by direct infection of cardiomyocytes, lung injury, or other unknown mechanisms. The gene expression profile of GSE150392 was obtained from the Gene Expression Omnibus (GEO) database. The processing of high-throughput sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…During the worldwide outbreak of COVID-19, the hIPSC-CM-EHT model has contributed to several types of investigations that: 1) mimicked myocardial injuries caused by SARS-CoV-2 infection ( Li et al, 2021 ; Perez-Bermejo et al, 2021 ; Salerno et al, 2021 ; Xie et al, 2022 ); 2) evaluated the safety of different types of vaccines including mRNA and adenovirus vaccines, especially across different ethnic populations with different genomic backgrounds ( Bojkova et al, 2020 ; Lu et al, 2020 ; Davidson et al, 2021 ); and 3) assessed the potential side effects of anti-COVID-19 developed treatments on cardiomyocytes ( Charrez et al, 2021 ; Deguchi et al, 2021 ; Dimai et al, 2021 ). Research involving the hIPSC-CM-EHT model in COVID-19 has rapidly extended the application of hIPSC, making it a more common conceptual and powerful investigative tool.…”
Section: Application Of the Human-induced Pluripotent Stem Cells-deri...mentioning
confidence: 99%
“…During the worldwide outbreak of COVID-19, the hIPSC-CM-EHT model has contributed to several types of investigations that: 1) mimicked myocardial injuries caused by SARS-CoV-2 infection ( Li et al, 2021 ; Perez-Bermejo et al, 2021 ; Salerno et al, 2021 ; Xie et al, 2022 ); 2) evaluated the safety of different types of vaccines including mRNA and adenovirus vaccines, especially across different ethnic populations with different genomic backgrounds ( Bojkova et al, 2020 ; Lu et al, 2020 ; Davidson et al, 2021 ); and 3) assessed the potential side effects of anti-COVID-19 developed treatments on cardiomyocytes ( Charrez et al, 2021 ; Deguchi et al, 2021 ; Dimai et al, 2021 ). Research involving the hIPSC-CM-EHT model in COVID-19 has rapidly extended the application of hIPSC, making it a more common conceptual and powerful investigative tool.…”
Section: Application Of the Human-induced Pluripotent Stem Cells-deri...mentioning
confidence: 99%
“…The study by Navaratnarajah et al (2021) also compared the GSE184715 and GSE150392 datasets and found that SARS-CoV-2 infection of hiPSC-CMs resulted in a significant down-regulation of the expression of cardiomyocyte skeletal proteins [5]. In previous bioinformatics studies, the results of the analyses have been presented mechanistically without addressing the whole molecular biological process [6][7][8]. The novelty of this study is to appropriately portray the complete molecular biological process of SARS-CoV-2 infection of hiPSC-CMs at the bioinformatics level.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them show that B-type natriuretic peptide (BNP) as a predictive marker of the severity of COVID-19 disease [ 11 ]. Thus, genes and signaling pathways involved in the myocardium infected by SARS-CoV-2 were subsequently identified highlighting the mechanisms underlying cardiac damage [ 12 ]. Furthermore, numerous studies have revealed a key role for the angiotensin converting enzyme-2 (ACE2) receptor, whose physiological balance is altered by SARS-CoV-2, by activating angiotensin II (Ang II)/Ang II receptor type 1 (AT1R) pathways and by leading to severe disease complications [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%